Integrative Analysis of Left Ventricle and Epicardial Adipose Tissue Identifies SDHA and OGDH as Candidate Targets for Ischemic Heart Disease - Arif, Muhammad (University of Gothenburg, 2026)
Sample Collections from Human SubjectsCardiac ischemic biopsies were obtained from 30 patients undergoing coronary artery bypass surgery at the Sahlgrenska University Hospital, Gothenburg, Sweden, due to significant atherosclerotic blockage in the epicardial coronary arteries. The surgery and sample collections were performed between 7 February 2013 and 1 February 2017. All patients were examined through echocardiography prior to operation, and the ejection fraction (EF) was measured. Non-ischemic biopsies from the left ventricle were obtained from 14 subjects undergoing aortic valve replacement in the same hospital, with angiography verified absence of coronary artery disease in any of the major myocardial coronary artery branches. Individual level data on age, sex, and other information is available in Data S1. All biopsies were collected from the left ventricle septum region with a 1 mm needle. The average weight of collected tissues samples was 100 mg and these were stored at -80°C until analysis. All patients gave informed and written consent. Patient characteristics (including diabetes status) were either collected as the patients entered the study or retrieved later from their medical charts. The diagnoses were based on ICD-codes from patient records and national databases. The study was approved by the Gothenburg Regional Ethics Committee and done according to the Declaration of Helsinki (Dnr 064-14).

RNA extraction and sequencingTotal RNA was isolated from biopsies relating to 44 samples from the left ventricle using RNeasy Fibrous Tissue Mini kit (QIAGEN) and 24 samples from epicardial fat using RNeasy Lipid Tissue Mini kit (QIAGEN). These 68 samples were processed with SMARTer® Stranded RNA-Seq Kit (Takara Bio) for reverse transcription, generation of double stranded cDNA and subsequent library preparation. All libraries were quantified with the Fragment Analyzer using the standard sensitivity NGS kit (Agilent Technologies), pooled in equimolar concentrations and quantified with a Qubit Fluorometer (ThermoFisher Scientific), the library pool was further diluted and sequenced using 150 cycles on an Illumina NextSeq500.

Data and Code Availability• The processed transcriptomics data (raw counts and TPM), clinical, and demography data can be retrieved from Data S1.

• The code for the analysis and visualization (grouped based on the figure numbers) is available at https://github.com/muharif/2025.Arif_Doran_etal_IschemicHeartDisease.

• The data presented in this paper contain sensitive information that cannot be shared openly. Work on submitting the data to FEGA Sweden has been initiated. FEGA Sweden is a national node of the Federated European Genome-phenome Archive (FEGA), which allows data to be shared under controlled access. The datasets in FEGA Sweden are findable through the European Genome-phenome Archive web portal (https://ega-archive.org).
Keywords: Systems biology; Medical and Health Sciences; Medicin och hälsovetenskap; Biological Sciences; Biologi